Արցախի տեղանվանական համակարգի պատմության շրջանաբաժանման փորձ - Մարգարյան, Լուսինե (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Попытка периодизации топонимической системы Арцаха имеет целью выявление историко-лингвистических топонимов-реалий и закономерности развития их системы на основе анализа историко-лингвистических фактов. Периодизация проводится на основе трех принципов: 1. Принцип истории топонимической системы – истории всех ее отдельных этапов. 2. Принцип невозможности абсолютной периодизации. 3. Принцип прямой связи между возникновением топонимов и их изменением параллельно с историей народа. Учет этих принципов при проведении периодизации топонимической системы проводится по двум направлениям: 1) анализ топографических фактов и исторических реалий и характеристика их исторических пластов; 2) аргументирование стратификации языковых влияний посредством лингвистического анализа топонимов. The attempt to periodize the toponymic system of Artsakh is aimed at identifying historical and linguistic toponyms – realities and regularities of development of their system based on the analysis of historical and linguistic facts. Periodization is carried out on the basis of three principles: 1. The principle of the history of the toponymic system is the history of all its separate stages. 2. The principle of impossibility of absolute periodization.3. The principle of the direct connection between the emergence of toponyms and their change in parallel with the history of the nation. Consideration of these principles during the periodization of the toponymic system is carried out in two directions: 1. Analysis of the topographical facts and historical realities and characterization of their historical strata. 2. Argumentation of the stratification of linguistic influences through linguistic analysis of toponyms.
Keywords: Լեզվաբանություն